(untitled) (Tanzania Medical Journal, 2017)
This case report describes the variation of branches of the arch of the aorta. The variation was discovered from a male cadaver at St Joseph University during routine dissection of the structures within the thoracic cavity. We found the common trunk which arises from the arch of the aorta. This trunk eventually divided into two branches namely; the brachial cephalic trunk and the left common carotid artery. This is the deviation from the normal branching pattern of the arch of the aorta. Knowledge on this important vascular variation from the arch of the aorta is significant in both invasive surgical procedures and for diagnostic purposes of the thorax and areas of the head and neck. During endovascular procedures, we insert the catheter through femoral artery to the abdominal aorta and further to the arch of the aorta. Awareness of the variation is therefore important as the above mentioned technique may be difficult to perform in case of the anatomical variations of the arch of the aorta. This type of variation is very rare and hence knowledge of such variations is of prime importance to surgeons, cardiologist and interventional radiologist during surgeries or any other imaging procedures.